Adaptive Strategies and Evolutionary Responses of Microbial Organisms to Changing Oceans - Arromrak, Bovern Suchart; Li, Zhenzhen; Gaitán-Espitia, Juan Diego (Frontiers in Marine Science, 2022)
Environmental variability is an intrinsic characteristic of nature. Variability in factors such as temperature, UV, salinity, and nutrient availability can influence structural and functional properties of marine microbial organisms. This influence has profound implications for biochemical cycles and the ecosystem services provided by the oceans. In this review we discuss some of the most relevant mechanisms underpinning adaptive strategies of microbial organisms in variable and dynamic oceans. We assess the extent to which the magnitude and rate of environmental change influence plastic phenotypic adjustments and evolutionary trajectories of microbial populations. This understanding is fundamental for developing better predictions regarding microbial dynamics at ecological and evolutionary time-scales and in response to climate change.